What makes an EHR "open" or interoperable?. (13th June 2015) - Sittig, Dean F; Wright, Adam
Abstract: We have identified 5 use cases that comprise a useful definition of an "open or interoperable electronic health record (EHR)." Each of these use cases represents important functionality that should be available to 1) clinicians, so they can provide safe and effective health care; 2) researchers, so they can advance our understanding of disease and health care processes; 3) administrators, so they can reduce their reliance on a single-source EHR developer; 4) software developers, so they can develop innovative solutions to address limitations of current EHR user interfaces and new applications to improve the practice of medicine; and 5) patients, so they can access their personal health information no matter where they receive their health care. Widespread access to "open EHRs" that can accommodate at least these 5 use cases is important if we are to realize the enormous potential of EHR-enabled health care systems.